Clinical characteristics and mortality risk factors of mixed bacterial infections in hematopoietic stem cell transplantation recipients - Liu, Yanfeng; Liu, Yi; Chen, Xuefeng; Jia, Yan (Frontiers in Cellular and Infection Microbiology, 2023)
Background and Objective: Mixed bacterial infections (MBI) is one of the complications after hematopoietic stem cell transplantation (HSCT) and increases the risk of patient death. However, there are few reports specifically on this topic. The purpose of this study was to investigate the clinical characteristics and mortality risk factors of MBI in HSCT recipients. Methods: The electronic medical records of patients undergoing HSCT were collected. The epidemiological features and antibiotic resistance of patients with and without MBI were compared. Logistic regression and Cox regression were used to identify the risk factors for MBI acquisition and death. R language was used to construct a prediction model for the overall survival of HSCT recipients with MBI. Results: The cumulative incidence of MBI was 6.3% and the mortality was 48.8%. Time interval from diagnosis to transplantation > 180 days (HR=2.059, 95% CI 1.042-4.069, P=0.038) and ICU admission after transplantation (HR=2.271, 95% CI 1.053-4.898, P=0.036) were independent risk factors for MBI acquisition. Engraftment period > 20 days (HR=2.273, 95% CI 1.028-5.027, P=0.043), continuous renal replacement therapy (HR=5.755, 95% CI 1.691-19.589, P=0.005) and septic shock (HR=4.308, 95% CI 2.085-8.901, P=0.000) were independent risk factors associated with mortality. Conclusions: MBI has become a serious problem that cannot be ignored after HSCT. It is urgent for clinicians to pay high attention to it and formulate reasonable monitoring and treatment plans to improve the prognosis of patients.